PROFILE OF INCOMPATIBLE REACTIONS TO PACKED RED CELL TRANSFUSION IN PATIENTS WITH CHRONIC KIDNEY DISEASE AT SANGLAH HOSPITAL - Arsana, I Nyoman; Puspa Adi , Ni Nyoman Sri; Juliasih, Ni Ketut Ayu (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: Since the prevalence of chronic renal failure disease has increased. Packed Red Cell (PRC) transfusions were a common way to replace the kidneys' function in filtration. However, the reaction caused was not widely reported. Purpose: To assess the profile of incompatible reactions in PRC transfusions of chronic kidney disease patients at Sanglah Hospital, Denpasar. Method: A descriptive observational study with a cross-sectional design was employed to identify incompatibility reactions in 210 patients using medical records from July–December 2021 at Sanglah Hospital in Denpasar. Sample determination using saturated sampling techniques and data analysis were carried out descriptively. Result: Incompatible reactions in patients with chronic renal failure at Sanglah Hospital Denpasar still affected 57 people (27.14%) out of 210 people with chronic renal failure. This condition could increase fatalities in various health services if not appropriately handled. Incompatible reactions could occur, and the higher risk was in patients of the male sex who were elderly (45–65 years), had blood type O, had hemoglobin (Hb) levels ranging from 6.1–9.0 g/dL, and had conducted PRC transfusions above three pouches with a frequency of more than three times. Conclusion: People with chronic kidney failure still had a high chance of having an incompatible reaction after a PRC transfusion. Many different things caused these reactions. Incompatibility reactions in people with chronic kidney failure should happen less often in the future if they were evaluated and found early.